(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
This work includes the results of studies about the state of the secondary protection against corrosion to ensure the building metal structures’ durability. The task of preserving the qualitative and quantitative indicators under the influence of the aggressive atmosphere in industrial enterprises is being solved. Methodology. The technique of improving the efficiency of the means technology and methods of metal structures secondary protection from corrosion during the technical condition monitoring is stated. Results. The developed diagnostic procedures include statistical accounting and the corrosion state monitoring of metal structures, identifying the causes of the occurred defects and damage. The basis of prediction for service life and reaching the limit states are determined by the level of vulnerability and threats, taking into account the actual state. Scientific novelty. A procedure for servicing structures based on the actual state has been developed. The procedure for drawing up specifications of corrosion protection measures according to the criterion of corrosion hazard has been determined. It makes possible to meet the requirements for the reliability of building metal structures, to prescribe technological safety management measures during the established service life of construction objects. Practical significance. The proposed generalized indicators of the actual structures’ corrosion state determine the structure’s operability as a whole. The functional dependencies between the operability of the main and auxiliary structures are established. The relationship between the values of corrosion resistance indicators and metal structures durability are determined. Actual technical condition control consists of checking that the values of these indicators are within acceptable limits. Taking into account the degree of operating environment aggressiveness is one of the determining factors in order to ensure the secondary protection effectiveness against corrosion. This procedure is the basis for the rational specifications appointment for anti-corrosion protection systems with subsequent display in the design and technological documentation.